Marx, keynes and the possibility of crisis (1992)
In this article Peter Kenway states that the theories developed by Marx and Keynes to explain the operation of the capitalistic economy complement each other. Due to the existence of money, in Marx the economic crisis is always a possibili ty that may occur when a rupture in the capi tal circuit separates the act of purchasing from the act of selling. This possibilityarises from the anarchy of capitalistic production, its basiccharacteristic, and raises questions on the demand level required in orden to carry it out. Keynes' theory of the effective demand asserts that the crisis occurs when the inflows and outflows of investment do not provide the sufficient aggregated demand to carry out the productoAccording to the author, the common characteristic to both approaches in then, the attempt to build a new monetary theory of capitalistic production, in which the theory of possibility supplements that of effective pemand in the explanation of why money performs an operative role in the production process. In turn, the theory of effective demand supplements the theory of possibili ty to explain the demand level required to carry out the product between the various departments of the economy. Thus, in the analysis by Kenway, Marx and Keynes share the same area regarding the theory of a possibility of a crisis. The theory of  reality would be the subject for another analysis.